Deterioration of stone and concrete exposed to bird excreta – Examination of the role of glyoxylic acid. (November 2017) - Dyer, Thomas
Abstract: The deterioration of buildings as a result of the deposition of bird excreta is a phenomenon which has been well-documented. A number of mechanisms have been proposed as playing a role in deterioration, some of which involve biological processes. Uric acid in bird excreta is broken down by fungi into urea and glyoxylic acid. This paper examines the effect of exposing stone and cement specimens to glyoxylic acid solutions. These materials were a limestone, a sandstone and two cement pastes – Portland and calcium sulfoaluminate cement. Specimens of these materials were submerged in acid solutions and deterioration characterised using mass loss measurements, micro-CT scanning, and analysis of the solutions at the end of the experiment and the acid-degraded layers at the specimen surface. Attempts were made to synthesise and characterise calcium salts of glyoxylic acid. Additionally, geochemical modelling was conducted to provide further understanding of the deterioration processes. The results indicate that the main processes involved in glyoxylic acid attack of the materials investigated are acidolysis and complex formation. No calcium glyoxylate salts were present in the degraded materials. Instead, a conversion of glyoxylate to oxalate occurred leading to precipitation of calcium oxalate compounds. Highlights: Portland cement most susceptible to glyoxylic attack, followed by CSA cement and limestone. Mechanisms of deterioration are acidolysis and complex formation. Glyoxylate is converted to oxalate during its interaction with calcium-bearing materials.